The possibilities of using the playing of recorder in the music teaching for the first grade pupils - Kepule, Iveta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The goal of the paper is to evaluate and propose methodological techniques for the introduction of the playing of recorder in the music teaching for the first grade pupils, in order to more successfully develop the basic singing skills. Methods: analysis of the teaching and psychological literature regarding the possibilities of playing the recorder in the music teaching, observation and analysis of the process of music teaching and the reflection on the personal experience in connection with the standard of the General education of Latvia in the music teaching. Analysis of the informal discussion based on the use of playing of recorder in the music lesson. Modeling of the pupils’ practical activities in music teaching in the primary school. Results: Methodological techniques are proposed for the development of the basic singing skills using the playing of recorder, and the creation of the cooperation among the students and their self-expression skills in the music lessons is encouraged. A teacher starting the formation of the basic singing skills often in the teaching process faces the situation, when the majority of the pupils in the class have an insufficiently developed ability to listen and reproduce the sound using their voice. One of the goals of the music teaching is to create correct vocal skills of the pupils, placing an emphasis on proper inhalation, creation of sound and also on a posture. Correct breathing is important both for singing and playing the recorder, but the tune culture is formed by the interaction of the breathing and posture. These singing aspects have the common characteristics with the basics of playing the recorder: interaction of breathing and posture forms the timbre of the recorder’s sound. The pupils initially cannot physically sing a certain pitch, but playing of recorder helps them to obtain a certain pitch of the sound using their hands, thereby allowing hearing and reproducing the sound, while simultaneously developing preconditions for the composition of stable melody in the playing of recorder. The pupils acquire the note reading skills simultaneously with the learning of proper breathing and blowing in. In order for the pupils to easier comprehend the recording of the note rhythm, they are offered to play simple rhythm examples, gradually increasing the number of ledger lines until a full staff is reached. Such method of learning to read the notes allows comprehending that the same melody can be played at different pitches. Any sound is always perceived and processed together with its duration and timbre (Griffin, 2007), so the combination of the sound of playing the recorder and singing gives an additional impulse to the pupils’ auricular centre. The timbral differences of the sounds of recorder and human voice are processed in different areas of the brain – the secondary and associative; therefore it is reasonable to assume that the combination of playing the recorder and singing stimulates the brain activity, based on the research of M. Tervaniemi and I. Winklera (Tervaniemi & Winklera, 1997). The use of the playing of recorder in teaching music is not new in the music education. In the middle of 20th century, it was popularized in their philosophies of teaching music by Karl Orff, Schinichi Suzuki and Zoltan Kodaly. The playing of recorder is not difficult, it does not create problems for the pupils, but brings them joy and satisfaction about their playing skills. This factor is therefore one of the most important for the creation of positive self-expression skills and motivation during the music lesson. Based on the opinion of B. Teplov (Теплов, 1947), the musical talent is formed in the childhood and it manifests itself in the pupil’s attitude towards the music: he or she likes or dislikes it. Combining the singing skills with the playing of recorder in the music lesson brings the joy to the pupils about their ability to play and creates the positive motivation. A teacher develops a vocal and instrumental musical score, encouraging all pupils to participate in playing music, thereby creating a situation, when each pupil achieves a positive result in accordance with his or her specific playing skills. The creation of skills to play in the group is equally important. Learning to read the notes in the staff is the beginning for the creation of polyphony in the music teaching. The teacher using the singing and playing of recorder skills may form the vocal, vocal and instrumental or instrumental groups. The pupils during the playing of recorder listen to the pitch of the sound and form a precise musical sound of the recorder.The goal of the study: to find out the opinion of the teachers of music regarding the possibilities to use the playing of recorder in teaching music. The methods used in the study: informal discussion of the target group. The group at the beginning of the discussion is asked to share its experience and provide the comments regarding the use of playing of recorder in teaching music. The following results were gathered after summarizing the opinions and arguments expressed during the discussion of the group: all members of the target group are familiar with the playing of recorder; 5 respondents admit that they play the recorder, 2 respondents have the basic skills of playing the recorder, and 1 respondent does not know how to play the recorder; 4 respondents use the playing of recorder in music teaching, but only one respondent has used the elements of playing the recorder in teaching of the singing skills; 1 respondent has decided to use the playing of recorder in music teaching during the next school year; all respondents consider the playing of recorder as a supplemental method, which can be used in music teaching; all respondents admit that the playing of recorder facilitates the development of pupils’ musical hearing; 6 respondents believe that the learning to play the recorder in a music lesson is a time – consuming learning method, because there is already limited time for teaching the curriculum; 3 respondents using the recorder in the teaching process believe that the introduction of playing the recorder in the music teaching is not useful, because the recorders available to the pupils do not allow playing in unison; 1 respondent expressed an opinion that the playing of recorder can be used in the music lesson only by working with a previously prepared selection of pupils. The following negative and positive arguments were gathered after summarizing the opinions and arguments provided during the group discussions: the pupils buy the recorders manufactured by different companies, therefore their timbral sound may differ, and the pitches of the sounds, which are not always identical, do not allow reaching a perfect unison; different fingering of the recorders (German recorders and baroque recorders) makes the learning process difficult. The pupils observing each other’s finger movements often learn to play incorrect pitches of the sounds, which are difficult for the teacher to control during the beginning stage of learning to play the recorder. traditional teaching methods are more useful and easier to apply in music teaching. The teachers of music relying on their personal experience, however, confirm the positive aspects of using the playing of recorder in teaching music for the first grade pupils: playing of recorder facilitates the development of the pupils’ musical achievements, especially the development of musical hearing of the pupils; facilitates the development of the pupils’ self-expression skills, because playing of recorder allows each pupil accomplishing his/her individual artistic potential. the playing of recorder in teaching music facilitates the development of the pupils both from the teaching and psychological point of view. It can be concluded by comparing the musical development of the pupils from 3 different classes that the musical development is the highest in the classes using the playing of recorder in their music lessons. This conclusion is also affirmed by the number of pupils in each class participating in the groups of amateur performance. The number of such pupils is the highest in the classes with the elements of playing the recorder in teaching music. Therefore it can be concluded that the process of teaching music creates a positive motivation, which facilitates the necessity for an emotional musical experience for pupils, as well as the tendencies of creation of a collective body of the class and the cooperation skills among the pupils.